Pengembangan Media Pembelajaran Berbasis Kvisoft Pada Materi Ekosistem Bermuatan Literasi Lingkungan Untuk Siswa Kelas X SMAN 1 Tebing Tinggi - ., Sutria; ., Ira Suryani; ., Efrida Pima (CV. ITTC INDONESIA, 2023)
This study aims to develop-based learning media Kvisoft on ecosystem materials containing environmental literacy, test the feasibility of the media and find out the obstacles experienced during the development process. This study uses the ADDIE model of research and development (R&D) (Analysis, Design, Development, Implementation, and Evaluation). The test subjects in this study were students of class X MIA 1 and 2 of SMAN.1 Tebing Tinggi. The trial was carried out in small groups to 15 students and large group trials to 60 students to determine the response to the media assessment through the response questionnaire instrument sheet. Based on the results of media expert validation, the overall aspect obtained an average percentage of 91.42% with a very decent category. The results of material expert validation obtained an average percentage of 72.56% with a feasible category. The results of the validation of linguists obtained an average percentage of 85.41% with a very feasible category. The results of the teacher's assessment response obtained an average percentage of 92.2% with a very decent category. The results of the student assessment responses in the small group trial obtained an average percentage of 94.26% and in the large group trial the average percentage was 92.83% with a very decent category. Thus, based learning media Kvisoft on ecosystem materials containing environmental literacy are very suitable for teachers and students to use in the biology learning process.